The Economic Potential of Aceh Cattle Based on Its Farmers, Traders, and Consumers Perspective - Sofyan, Hamny; Sudarnika, Etih; Satyaningtijas, Aryani S.; Sumantri, Cece; Agungpriyono, Srihadi (Frontiers in Sustainability, 2020)
This study aims to evaluate the economic potential of Aceh cattle from the perspective of stock farmers, traders, and consumers as the three main players in the business. This study was conducted from June to August 2018 in Banda Aceh City and Aceh Besar District, Aceh Province, Indonesia. It used related literature and a survey method that involved interviews, observations, and questionnaires from 9 stock farmers, 23 traders, and 22 consumers to obtain data. The data presented descriptively and analyzed using SWOT (strengths, weaknesses, opportunities, and threats) analysis. The results show that the strength factors of the Aceh beef business are high selling prices, easy maintenance, the good taste of meat, and that do not shrink quickly when cooked. Meanwhile, the weakness factors are the limitation of the availability of seeds, traditional methods of assessing carcass weight during the buying and selling process, and the low productivity of the cattle compared with other breeds. The factors that become opportunities include the high demand for the beef, on both weekdays and religious holidays, the selling price tends to increase each year, and the government's commitment to increase local cattle productivity through various programs. However, there are certain threats to the development of these cattle, and they include the high price of calves, competition with other more productive breeds, the existence of other cheaper sources of animal protein, and a decrease in consumer purchasing power. The difference between the value of the strength and weakness factors was 0.12, which signified a positive result, while that between the opportunity and threat factors was −0.29, which signified a negative result. Furthermore, the coordinate value from the Cartesian field shows that the development of these cattle is in quadrant IV, which means that the prospect for development is still quite high, regardless of the threat. In conclusion, Aceh cattle have a high economic potential to be developed, which needs to be strengthened through the rebranding program while at the same time maintaining the sustainability of the Aceh cattle breed in Indonesia. Meanwhile, the government is expected to supervise and regulate the trade of these cattle to provide beef at an affordable price for consumers.